Molecular detection of the oyster parasite Mikrocytos mackini, and a preliminary phylogenetic analysis - Carnegie, Ryan; Meyer, Gary; Blackbourn, Janice; Cochennec, Nathalie; Berthe, Franck; Bower, Susan (Diseases of Aquatic Organisms, 2003)
The protistan parasite Mikrocytos mackini, the causative agent of Denman Island disease in the oyster Crassostrea gigas in British Columbia, Canada, is of wide concern because it can infect other oyster species and because its life cycle, mode of transmission, and origins are unknown. PCR and fluorescent in situ hybridization (FISH) assays were developed for M mackini, the PCR assay was validated against standard histopathological diagnosis, and a preliminary phylogenetic analysis of the M mackini small-subunit ribosomal RNA gene (SSU rDNA) was undertaken. A PCR designed specifically not to amplify host DNA generated a 544 bp SSU rDNA fragment from M mackini-infected oysters and enriched M. mackini cell isolates, but not from uninfected control oysters. This fragment was confirmed by FISH to be M mackini SSU rDNA. A M mackini-specific PCR was then designed which detected 3 to 4x more M mackini infections in 1056 wild oysters from Denman Island, British Columbia, than standard histopathology. Mikrocytos mackini prevalence estimates based on both PCR and histopathology increased (PCR from 4.4 to 7.4%, histopathology from 1.2 to 2.1%) when gross lesions were processed in addition to standard samples (i.e. transverse sections for histopathology, left outer palp DNA for PCR). The use of histopathology and tissue imprints plus PCR, and standard samples plus observed gross lesions, represented a 'total evidence' approach that provided the most realistic estimates of the true prevalence of M mackini. Maximum parsimony and evolutionary distance phylogenetic analyses suggested that M mackini may be a basal eukaryote, although it is not closely related to other known protistan taxa.